The Image of Europe in Nikolay Karamzin’s “Letters of a Russian Traveller” - Váradi, Ferenc (Slavica, 2026)
“Russia or Europe?” Nikolay Mikhailovich Karamzin undertook a journey to Western Europe and, whilst travelling, wrote travel letters describing his impressions. In Russian literature, even before Karamzin, there were works of travel literature written for the purposes of pilgrimage or trade, but in the 18th century the emphasis shifted to enlightenment and to the description of the national characters of the peoples of Western Europe. How does the Russian traveller perceive Western Europeans, how does he describe representatives of Western nations, and what does he pay attention to upon arriving in a foreign city? This article seeks to answer these questions.